Potencial antinociceptivo do (-)-bisabolol: avaliação comportamental e análise eletrofisiológica em nervo isquiático de camudongos - Alves, Aron de Miranda Henriques (2009)
(-)-Bisabolol is a sesquiterpene alcohol found as the major constituent of the essential oil from German chamomile (Chamomilla recutita (L.) Rauschert), a plant used for centuries mostly for its medicinal properties. Previous studies stated that extracts of (-)- bisabolol-rich plants showed significant antinociceptive activity in experimental models of pain. Until this moment no literature reports concerning the activity of (-)-bisabolol on nociception nor on the sciatic nerve of rodents were found, therefore, the present work proposes to investigate the potential of this terrene as an antinociceptive agent in experimental models in vivo and its relation towards nerve excitability reduction by using the single sucrose gap model adapted for mice sciatic nerve. In the acetic acid-induced writhing test it was observed that mice showed a significant decrease in the number of writhes when 25 mg/kg and 50 mg/kg of (-)bisabolol were administered (i.p.). It was also demonstrated that (-)-bisabolol inhibited the nociceptive response in mice treated with a dose of 50 mg/kg on the first phase of the formalin test and in mice treated with doses of 25 mg/kg and 50 mg/kg (i.p.) on the second phase of this test. In the electrophysiological assays it was verified that (-)-bisabolol acts on peripheral nervous system reducing the compound action potential (CAP) amplitude in a time-incubation and concentration-dependent manners, showing an IC50 of 8,2 mM. It was also observed that (-)-bisabolol promoted alterations in the evaluated CAP depolarization parameters amplitude (VPAC) and depolarization velocity (DVPAC) similarly to lidocaine, a standard voltage-gated sodium channels (Nav) blocker. Moreover, this sesquiterpene did not induce significant changes on the CAP repolarization phase, dissimilarly from 4-aminopyridine, a voltage-gated potassium channels (Kv) blocker. These results allow us to suggest a possible Nav blocker-like effect of (-)-bisabolol. Therefore, the presented results in this study have evidenced a promising antinociceptive-like effect of (-)-bisabolol, which might be associated, at least in part, with decreased peripheral neuronal excitability.